L‐mimosine increases the production of vascular endothelial growth factor in human tooth slice organ culture model. (28th June 2014) - Trimmel, K.; Cvikl, B.; Müller, H.‐D.; Nürnberger, S.; Gruber, R.; Moritz, A.; Agis, H.
Abstract Aim To assess the pro‐angiogenic and pro‐inflammatory capacity of the dentine–pulp complex in response to the prolyl hydroxylase inhibitor L‐mimosine in a tooth slice organ culture model. Methodology Human teeth were sectioned transversely into 600‐μm‐thick slices and cultured in medium supplemented with serum and antibiotics. Then, pulps were stimulated for 48 h with L‐mimosine. Pulps were subjected to viability measurements based on formazan formation in MTT assays. In addition, histological evaluation of pulps was performed based on haematoxylin and eosin staining. Culture supernatants were subjected to immunoassays for vascular endothelial growth factor (VEGF) to determine the pro‐angiogenic capacity and to immunoassays for interleukin (IL)‐6 and IL‐8 to assess the pro‐inflammatory response. Interleukin‐1 served as pro‐inflammatory control. Echinomycin was used to inhibit hypoxia‐inducible factor‐1 (HIF‐1) alpha activity. Data were analysed using Student's t‐test and Mann–Whitney U test. Results Pulps within tooth slices remained vital upon L‐mimosine stimulation as indicated by formazan formation and histological evaluation. L‐mimosine increased VEGF production when normalized to formazan formation in the pulp tissue of the tooth slices (P < 0.05). This effect on VEGF was reduced by echinomycin (P < 0.01). Changes in normalized IL‐6 and IL‐8 levels upon treatment with L‐mimosine did not reach the level of significance (P > 0.05), whilst treatment with IL‐1, which served as positive control, increased IL‐6 (P < 0.05) and IL‐8 levels (P < 0.05). Conclusions The prolyl hydroxylase inhibitor L‐mimosine increased VEGF production via HIF‐1 alpha in the tooth slice organ culture model whilst inducing no prominent increase in IL‐6 and IL‐8. Pre‐clinical studies will reveal if these in vitro effects translate into dental pulp regeneration.